Magnitudes and trends of Argentinian childhood malnutrition during the first decade of the twenty-first century - Longhi, Fernando (Población y Salud en Mesoamérica, 2015)
In this article the main magnitudes and trends that characterize childhood malnutrition in Argentina in the early years of this century are presented. To address this problem we developed an indicator called Integral Rate of Mortality in Childhood Malnutrition (TIMDN), an indicator of mortality which includes the direct causes of malnutrition (kwashiorkor, marasmus, etc.) as those associated with this problem, often contributory to nutritional frame. Prominent among these contributory causes we found: infectious diseases, diarrhea, measles, parasitism, bronchiolitis, and pneumonia, among others. The multi-scale analysis (diachronic and synchronic) has detected gaps, asymmetries and different behaviors in both the provincial and regional levels. Indeed, it was observed that while the national rate decreased, there have operated different regional behaviors, with different magnitudes and trends, as well as different provincial behaviours, with some cases of stagnation and increased malnutrition, contrary to what operated in the national framework and related contrast with epidemiological transition process, designated for the Argentine case. With the founded results, it is expected to collaborate in the implementation of specific public policies to reduce and / or to eliminate the problem of malnutrition in the provinces, meeting the specific needs for each territory.